A Simplified procedure for total DNA isolation from coldwater fish, Schizothorax richardsonii (Gray) - Kapila, Rajeev; Mishra, D P (Indian Journal of Fisheries, 2011)
Isolation of good quality genomic DNA with desired yield is mandatory for conductingresearch in molecular biology. Various protocols for isolation of totalDNA from fish tissues have been applied using different buffers, detergentsand enzymes. Under the present investigation a simplified method for totalDNA isolation from muscle tissues of coldwater fish, Schizothorax richardsoniihas been developed using N-Lauroyl sarcosine (sarcosyl) as a detergent. DNAyield (45Î¼g /100 mg of fresh muscles) obtained by this method was significantlyhigher (P